Reverend Addie Wyatt: Faith and the Fight for Labor, Gender, and Racial Equality - Rocksborough-Smith, Ian (Labour / Le Travail, 2017)
This article reviews the book, "Reverend Addie Wyatt: Faith and the Fight for Labor, Gender, and Racial Equality," by Marcia Walker-McWilliams.